Study of argon assimilation into the post-disruption runaway electron plateau in DIII-D and comparison with a 1D diffusion model. (21st August 2019) - Hollmann, E.M.; Eidietis, N.W.; Herfindal, J.L.; Parks, P.B.; Pigarov, A.Y.; Shiraki, D.; Austin, M.E.; Bardoczi, L.; Baylor, L.; Bykov, I.; Carlstrom, T.N.; Kaplan, D.; et al.
Abstract: The assimilation of argon injected into post-disruption runaway electron (RE) plateaus is studied and compared to the vertical loss rate for vertically unstable RE plateaus. A 1D diffusion model is developed to include neutral diffusion and ionization and is used to help in data interpretation. It is found that the radial mixing time scale of argon ions ( 0.05 s) is comparable to the vertical loss timescale. Neutral argon becomes the dominant Ar species in the RE plateau for large Ar numbers ( ); at the same time the neutral Ar diffusivity decreases due to plasma cooling, causing a saturation in the assimilation of injected Ar on the vertical loss time scale. Injection of Ar into vertically unstable RE plateaus in DIII-D does increase the vertical loss rate, as predicted by previous modeling of ITER. However, there is a decreasing trend in RE current at the wall strike as the Ar quantity is turned up or as the Ar is injected earlier, indicating a decrease in RE energy deposited to the wall.